Perspective: Spectrin-Like Repeats in Dystrophin Have Unique Binding Preferences for Syntrophin Adaptors That Explain the Mystery of How nNOSμ Localizes to the Sarcolemma - Percival, Justin M. (Frontiers in Physiology, 2018)
Dystrophin is a massive multi-domain protein composed of specialized amino and carboxyl ter-mini that are separated by 24 spectrin-like repeats. Dystrophin performs critical structural and signaling roles that are indispensable for the functional integrity of skeletal muscle. Indeed, the loss of dystrophin protein expression causes the muscle wasting disease, Duchenne muscular dystrophy (DMD). Substantial progress has been made in defining the functions of the domains of dystrophin, which has proven invaluable for the development of miniaturized dystrophin gene and exon skipping therapies for DMD. However, a long-standing mystery regarding dystrophin function is how dystrophin, and its adaptor and neuronal nitric oxide synthase mu (nNOSmu) binding partner alpha-syntrophin, cooperate to localize nNOSmu to the sarcolemma. Only when localized to the sarcolemma can nNOSmu override sympathetic vasoconstriction and prevent functional ischemia in contracting muscles. Current evidence suggests that spectrin-like repeat 17 of dystrophin, and alpha-syntrophin cooperate to localize nNOSmu to the sarcolemma. However, the exact mechanism remains unclear and controversial because of equivocal evidence for direct binding of dystrophin and nNOSmu. Recently, an important study identified a novel alpha-syntrophin binding site within spectrin-like repeat 17, leading to a new model whereby alpha-syntrophin recruits nNOSmu to the sarcolemmal dystrophin complex by binding spectrin-like repeat 17. This model appears to finally solve the mystery of the dual requirement for dystrophin and alpha-syntrophin for sarcolemmal nNOSmu localization. The aim of the current perspective is to highlight this major advance in understanding of dystrophin’s role in localizing nNOSmu and its broader implications.